Specialization in a Nitrogen-Fixing Symbiosis: Proteome Differences Between Sinorhizobium medicae Bacteria and Bacteroids - Svetlana, Y.; Yi Qu; Jennifer, T.R.; Nivethika, A.; Erika, M.Z.; Joseph, M.B.; Sam, P.; Mary, S.L.; Michael, L.K. (My University, 2021)
This material is based upon work supported by the United States Department of Energy (DOE), Office of Science, Office of Energy Physical Biosciences Program, under award number DE-FG03- 96ER20225. This work was supported by the Agricultural Research Cen ter at Washington State University in association with United States Department of Agriculture–National Institute of Food and Agriculture projects NP00773 and WNP00008. Portions of this research were sup ported by the DOE Office of Biological, Environmental Research Genome Sciences Program under the Pan-Omics project and Discovery Grant from the Natural Sciences and Engineering Research Council of Canada grant EGP 485260. The proteomic analysis was performed in the Environmental Molecular Science Laboratory, a DOE National Scientific User facility at Pacific Northwest National Laboratory in Richland, WA.
Keywords: Bacteria–plant interaction; Bacteroids; Flavoproteins; Microaerobic metabolism; Nitrogen fixation; Sinorhizobium–Medicago; Truncatula symbiosis; Sustainable agriculture; Tandem mass spectrometry